Digital-built environment: are our students ready for the next challenge? - Munianday, Praveena; Esa, Muneera; Abu Bakar, Ariza Syarikin; Abhari, Sara (GADING Journal for the Social Sciences, 2023)
Today, the Industrial Revolution 4.0 (IR4.0) is producing immense uncertainty. Innovations transform our way of life and our methods of working. In this era of technological upheaval, employees and fresh graduates are aware of the skills gap and the importance of digital literacy due to pervasive change across all industries. Future graduates, especially from Built Environment, should incorporate the 4th Industrial Revolution and move toward a digital-built environment. Digital-built environment is the application of innovative digital engineering technologies, such as 3D printing, digital scanning, remote sensing, and building information modeling, to boost efficiency and performance in the construction industry. Today, digital inclusion significantly depends on skills than on technology availability. Students in the 21st century must be proficient in digital skills. Although Malaysia has adopted a digital learning environment, indicators are not established to gauge current digital competency standards for higher education graduates. Hence, this paper aims to investigate the digital competencies of built environment students based on the COBADI 2.0 (Basic Digital Competencies/Registered Trademark 2970648) questionnaire. The survey was conducted with final year students from built environment fields at Universiti Sains Malaysia. These future graduates demonstrated an upper-intermediate level of information and digital literacy, including communication and teamwork, but a lower-intermediate level of digital content creation. This research promotes digital competence in higher education and improves teaching and learning in built environment.